A history of Islamic legal theories : an introduction to Sunnī uṣūl al-fiqh / Wael B. Hallaq. - Hallaq, Wael B., 1955- (Cambridge University Press, 1997)
Wael B. Hallaq has already established himself as one of the most eminent scholars in the field of Islamic law. In this book, first published in 1997, the author traces the history of Islamic legal theory from its early beginnings until the modern period. Initially, he focuses on the early formation of this theory, analysing its central themes and examining the developments which gave rise to a variety of doctrines. He concludes with a discussion of modern thinking about the theoretical foundations and methodology of Islamic law. In organisation, approach to the subject and critical apparatus, the book will be an essential tool for the understanding of Islamic legal theory in particular and Islamic law in general. This, in combination with an accessibility of language and style, will guarantee a readership among students and scholars and anyone interested in Islam and its evolution.